TEORI EVOLUSI AGAMA ANALISIS KRITIS TERHADAP PEMIKIRAN INTELEKTUAL BARAT ZAMAN MODERN (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2017)
There are three arguments to construct the theory of evolution of religion, such as: argument of degrees of human mind (theological-pilosophical-scientific), argument of quantity-being of god (animisme-polytheisme-monotheisme and argument of dinamical culture (primitive, archaic, historic, first modern, dan modern). Based on these arguments modern western intellectuals concluded that the religion has linearly been growing up with the growth of thought and culture of human life.